2003
DOI: 10.1038/sj.onc.1206227
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of multifocality of telomere erosion in high-grade prostatic intraepithelial neoplasia (HPIN) and concurrent carcinoma

Abstract: Mechanisms underlying prostate cancer (CaP) initiation and progression are poorly understood. A chromosomal instability mechanism leading to the generation of numerical and structural chromosomal changes has been implicated in the preneoplastic and neoplastic stages of CaP. Telomere dysfunction is one potential mechanism associated with the onset of such instability. To determine whether there was alteration in telomere length and chromosome number, 15 paraffin-embedded prostatectomy specimens were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 55 publications
(47 reference statements)
3
50
1
Order By: Relevance
“…Telomeres in tumor cells are different from telomeres in normal cells; they are generally shorter, even critically short [Vukovic et al, 2003;Meeker et al, 2004]. However, they may also be elongated or different subpopulations of telomere lengths may be present [Meeker et al, 2004].…”
Section: Telomere Organization In Tumor Cellsmentioning
confidence: 97%
“…Telomeres in tumor cells are different from telomeres in normal cells; they are generally shorter, even critically short [Vukovic et al, 2003;Meeker et al, 2004]. However, they may also be elongated or different subpopulations of telomere lengths may be present [Meeker et al, 2004].…”
Section: Telomere Organization In Tumor Cellsmentioning
confidence: 97%
“…In high-grade PIN, telomeres are also short in the vast majority of cases (40,41). Interestingly, Vukovic and colleagues found that PIN lesions near carcinoma often showed shorter telomeres than PIN lesions away from carcinoma (41).…”
Section: Molecular Biology Of Pinmentioning
confidence: 99%
“…10 This difference in rearrangements is at the origin of chromosomal evolution seen in many complex tumors that exhibit dynamic BBF cycles, such as osteosarcoma, and prostate, breast and colon cancer. [14][15][16][17][18][19][20][21] Aberrations in centrosome duplication cycles leading to centrosome amplification have been observed in many different cancers 22,23 and are another characteristic feature of RS cells. 1,[24][25][26] Thus due to the combination of telomere dysfunction, centrosome amplification and defective spindle formation, RS cells are expected to gain increasingly complex karyotypes with respect to their chromosome numbers, rearrangements and nuclear distribution among individual sub-nuclei of the multi-nucleated RS cell.…”
Section: Introductionmentioning
confidence: 99%